2018
DOI: 10.3390/ijms19113485
|View full text |Cite
|
Sign up to set email alerts
|

A Novel High Sensitivity Type II Collagen Blood-Based Biomarker, PRO-C2, for Assessment of Cartilage Formation

Abstract: N-terminal propeptide of type II collagen (PIINP) is a biomarker reflecting cartilage formation. PIINP exists in two main splice variants termed as type IIA and type IIB collagen NH2-propeptide (PIIANP, PIIBNP). PIIANP has been widely recognized as a cartilage formation biomarker. However, the utility of PIIBNP as a marker in preclinical and clinical settings has not been fully investigated yet. In this study, we aimed to characterize an antibody targeting human PIIBNP and to develop an immunoassay assessing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 45 publications
0
34
1
Order By: Relevance
“…Type II collagen is nearly exclusively localized to cartilage, being the major structural component of this tissue. Recently, immunoassays suitable for measuring serological collagen type IIB N-propeptide fragment (PIIBNP or PRO-C2) were developed and proposed for the estimation of cartilage formation [14].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Type II collagen is nearly exclusively localized to cartilage, being the major structural component of this tissue. Recently, immunoassays suitable for measuring serological collagen type IIB N-propeptide fragment (PIIBNP or PRO-C2) were developed and proposed for the estimation of cartilage formation [14].…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that PRO-C2 could serve as a biomarker not only for prediction of OA progression but also for treatment response. We recently demonstrated that FGF-18 induced PRO-C2 in both human and animal chondrocytes [14,32]. In addition, in the phase II FORWARD (FGF-18 Osteoarthritis Randomized Trial with Administration of Repeated Doses) study, intra-articular FGF-18 demonstrated a dose-dependent increase in the cartilage thickness on Magnetic Resonance Imaging (MRI) [33,34].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations